AVONET: morphological, ecological and geographical data for all birds. (24th February 2022) - Tobias, Joseph A.; Sheard, Catherine; Pigot, Alex L.; Devenish, Adam J. M.; Yang, Jingyi; Sayol, Ferran; Neate‐Clegg, Montague H. C.; Alioravainen, Nico; Weeks, Thomas L.; Barber, Robert A.; Walkden, Patrick A.; MacGregor, Hannah E. A.; et al.
Abstract: Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90, 020 individuals of 11, 009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity. Abstract : Existing morphological trait datasets for major taxonomic groups are highly incomplete, limiting their utility to ecologists and evolutionary biologists. We present a global dataset containing comprehensive morphological information, coupled with ecological and geographical variables, for all bird species. This detailed assessment of continuous trait variation across 11, 009 species offers a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.